Impact of Recurrent Miscarriage on Maternal Outcomes in Subsequent Pregnancy: The Mutaba’ah Study - Ali N; Elbarazi I; Ghazal-Aswad S; Al-Maskari F; Al-Rifai RH; Oulhaj A; Loney T; Ahmed LA (Dove Medical Press, 2020)
Nasloon Ali,1 Iffat Elbarazi,1 Saad Ghazal-Aswad,2 Fatima Al-Maskari,1,3 Rami H Al-Rifai,1,3 Abderrahim Oulhaj,1,3 Tom Loney,4 Luai A Ahmed1,3 1Institute of Public Health, College of Medicine and Health Sciences, United Arab Emirates University, Al Ain, United Arab Emirates; 2Obstetrics and Gynecology Department, Tawam Hospital, Al Ain, United Arab Emirates; 3Zayed Centre for Health Sciences, United Arab Emirates University, Al Ain, United Arab Emirates; 4College of Medicine, Mohammed Bin Rashid University of Medicine and Health Sciences, Dubai, United Arab EmiratesCorrespondence: Luai A AhmedInstitute of Public Health, College of Medicine and Health Sciences, United Arab Emirates University, PO Box 17666, Al Ain, United Arab EmiratesTel +971 37137511Email luai.ahmed@uaeu.ac.aePurpose: To estimate the prevalence of recurrent miscarriage (RM) and investigate the association between RM and adverse maternal outcomes in subsequent pregnancies.Participants and Methods: This is an interim analysis of a prospective study of 1737 pregnant women with gravidity of two or more prior to the current pregnancy. These women joined the Mutaba’ah Study between May 2017 and April 2019 and were followed up until they delivered. Hospital medical records were used to extract data on past pregnancy history and the progress and outcomes of the current pregnancy, such as gestational diabetes, preeclampsia, mode of delivery, preterm delivery, and complications at birth.Results: Amongst pregnant women with at least two previous pregnancies (n=1737), there were 234 (13.5%) women with a history of two or more consecutive miscarriages. Women with RM were slightly older, more parous, and more likely to have had previous infertility treatment (all p-values < 0.05). Women with a history of RM had independently significant increased odds of cesarean section (adjusted odds ratio (aOR) 1.81, 95% CI 1.24– 2.65) and preterm (< 37 weeks, aOR: 2.52, 95% CI 1.56– 4.08) or very preterm delivery (< 32 weeks, aOR: 7.02 95% CI 2.41– 20.46) in subsequent pregnancies than women who did not have a history of RM.Conclusion: Women with a history of RM were twice as likely to undergo cesarean section and seven times more likely to deliver prior to 32 weeks of gestation than women without a history of RM. The study findings support the need for early pregnancy monitoring or assessment units to ensure better follow-up and customized care for at-risk pregnant women with a history of RM.Keywords: cesarean section, cohort study, miscarriage, preterm delivery, recurrent miscarriage